Pengembangan Zonasi Sempadan Sungai Brantas Di Dermaga Joyoboyo Sebagai Kawasan Wisata Berbasis Sistem Informasi Geografi - Setyabudi, Irawan; Pratama, Wanda Andika; Kurniawan, Hendra (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Regional zoning planning is the initial stage of restructuring the Joyoboyo Pier area as a tourist area based on conservation principles. The principle of conservation in structuring tourist areas located in natural or natural areas is primarily an effort to protect natural resources and facilitate management. With zoning, it is hoped that tourism activities can run well because there is separation of land uses so that maximum land use can be achieved without interference from other land uses. So that a higher quality and environmentally friendly river border environment can be created. The aim of this research is to determine the zoning of the river border at Joyoboyo pier as a tourist area. This research method is a combined qualitative and quantitative method. Meanwhile, data analysis was carried out descriptively and spatially. The results of this research are the zoning of the Joyoboyo pier area with a core zone of 2.40 Ha (14%), a special zone of 2.69 Ha (15%), a buffer zone of 10.50 Ha (60%) and a utilization zone of 1 .94 Ha (11%). The development of river border zoning is the initial stage of establishing the Joyoboyo Pier Area as a tourist area which aims to create a higher quality and environmentally friendly river border and support community empowerment which can increase regional income.